2004
DOI: 10.1111/j.1348-0421.2004.tb03617.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Conditions Required for Structural and Functional Maturation of Rabies Virus Glycoprotein (G) in G cDNA‐Transfected Cells

Abstract: The spike projections of the rabies virion are composed of homotrimers of a single type of virus-coded glycoprotein (G) composed of 505 amino acids (1,11,35). The spike G proteins are involved in both the receptor recognition and binding to receptor molecules as well as in the low pH-dependent membrane fusion that occurs in the endosomes for releasing the viral ribonucleoprotein into the cytoplasm (30,31,34). As suggested from the experiments in which an amino acid substitution at position 333 of G protein str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In this study, we first confirmed the presence of two forms of rabies virus G protein that are detected under neutral pH conditions on the surface of the virion and infected cells, the 1-30-44 epitope-positive and -negative forms, which were tentatively termed the B and C forms, respectively. (In other words, the difference between the B and C forms is based on their reactivity to mAb #1- [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].) The ratio between the B and C forms was pH-dependent, and was the highest at pH 8.0.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we first confirmed the presence of two forms of rabies virus G protein that are detected under neutral pH conditions on the surface of the virion and infected cells, the 1-30-44 epitope-positive and -negative forms, which were tentatively termed the B and C forms, respectively. (In other words, the difference between the B and C forms is based on their reactivity to mAb #1- [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].) The ratio between the B and C forms was pH-dependent, and was the highest at pH 8.0.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, maturation of the G protein to a 1-30-44 epitope-positive B form was not easily accomplished in the G cDNA-transfected BHK cells, but was achieved in a few days' treatment with 2.5 mM sodium butyrate in the absence of other viral factors (32). In addition, as suggested in this study, the 1-30-44 epitope-positive conformation is not stable, whereby the G protein is prone to undergo structural changes to lose the 1-30-44 epitope-positive conformation even under neutral pH conditions, which is not yet enough, however, for acquiring the membrane fusion activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation